AI-Augmented Creative Writing: Evaluating Machine-Human Collaboration in Narrative Innovation - Ardi Azhar Nampira; Zhang Li; Wang Jing (Yayasan Adra Karima Hubbi, 2025)
This study examines how artificial intelligence (AI) can augment human creativity in the field of narrative writing through a collaborative approach. The research addresses the growing influence of AI-based tools in creative industries and the need to understand their role in enhancing innovation rather than replacing human authorship. The study aims to evaluate the effectiveness of machine-human collaboration in generating original and innovative storylines. Using a mixed-methods design, twenty creative writing teams were engaged in structured workshops combining generative AI tools with traditional writing processes. Data were collected from narrative outputs, participant observations, and post-workshop interviews, and analyzed using thematic coding and comparative quality assessment. Findings indicate that AI-assisted teams produced more diverse narrative structures and demonstrated a significant increase in creative risk-taking compared to control groups. The results suggest that AI can serve as a valuable co-creator when guided by intentional human direction. This research concludes that rather than replacing writers, AI technologies can strengthen creative processes, supporting a hybrid model where human judgment shapes and refines machine-generated contributions.